The methodological triangulation in research in Education Sciences - Juan Torres Guerrero; Juan Palomares Cuadros; Elisa Torres Ramos; Deysy Margarita Pérez Pérez (ADIDE Federación, 2008)
This article covers the investigation strategy which is carried out through a multi-method design. The investigation's aim consists of knowing the way Corporal Expression is treated in the Cuban Curriculum and in the field of Physical Education in actual practice in the province of Cienfuegos, Cuba. The work of the investigation is a quantitative study. The main aim consists of analyzing and interpreting the questionnaire that is used, also investigating the meaning thereof to teachers/professors and the different aspects from the results of the questionnaires: perceptions, attitudes, representations, opinions. This means it tries to enrich the quantitative analysis with a qualitative analysis that is based on a Focus group and on studying the applicable regulation. The combination of approaches allows the study of the subject from different angles, and in a significant/integral way. We present the results based on attaining the objectives of the study, comparing the statistic data with the investigation of the obtained qualitative data, as well as combine the data from the study of the regulation, presenting the most important results and concluding with some comments on the advantages of the use of combined techniques.